2023
DOI: 10.3390/s23125562
|View full text |Cite
|
Sign up to set email alerts
|

Plant and Salamander Inspired Network Attack Detection and Data Recovery Model

Abstract: The number of users of the Internet has been continuously rising, with an estimated 5.1 billion users in 2023, which comprises around 64.7% of the total world population. This indicates the rise of more connected devices to the network. On average, 30,000 websites are hacked daily, and nearly 64% of companies worldwide experience at least one type of cyberattack. As per IDC’s 2022 Ransomware study, two-thirds of global organizations were hit by a ransomware attack that year. This creates the desire for a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Federated learning has been used for network data security [4,30], healthcare data security [31], game theory [32], vehicular data [33,34], and smart city applications [35]. Studies have found that data poisoning attacks and other cyberattacks can also compromise this technique [36][37][38][39]. Furthermore, traditional machine learning approaches have a limited processing complexity and need help discovering complicated non-linear relationships in large datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Federated learning has been used for network data security [4,30], healthcare data security [31], game theory [32], vehicular data [33,34], and smart city applications [35]. Studies have found that data poisoning attacks and other cyberattacks can also compromise this technique [36][37][38][39]. Furthermore, traditional machine learning approaches have a limited processing complexity and need help discovering complicated non-linear relationships in large datasets.…”
Section: Introductionmentioning
confidence: 99%